The Influence of Religious Understanding on The Religious Moderation Attitude of Students at Muhammadiyah Schools In Jember - Rofi, Sofyan; Setiawan, Bahar Agus (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Religious moderation constitutes a popular terminology in the field of social and religious studies in Indonesia. The key point of this term concerns the manifestation of tolerance in social life, in addition to the equality of rights and humanity. The popularity of religious moderation is inseparable from the multicultural life of Indonesian society which is characterized with different religious beliefs. Muhammadiyah as a large religious organization in Indonesia has an important role and contribution in developing religious moderation in the life of many Muslims in the country. Many schools established by this organization have been designed and constructed on Islamic values as their philosophical basis for developing the curriculum. Hence, a number of subjects such as aqidah, akhlaq, and muamalah are always included as core content in these schools with the aim of fostering both knowledge and understanding of religion for students. The present study aimed thus to examine the influence of the dimensions of aqidah, akhlaq, and muamalah on students' religious moderation attitude in Muhammadiyah schools. The objectives of this study were simultaneously formulated in 4 hypotheses testing, 3 partial hypotheses, and one hypothesis. This research employed quantitative methods involving a multiple linear regression model. The instrument used in this study was a questionnaire containing 40 questions on the Linkert scale. Respondents were 255 students from 3 Muhammadiyah junior high schools. The results showed that the hypothesis was partial in that only the dimension of aqidah showed a significant effect. As for the simultaneous hypothesis testing, the f-count value is 31.319 > f-table 2.64, with an influence value of 0.522 and a significant contribution of 27.2 percent on the R-square value.